Analysis Of Community Satisfaction Index On Public Services In Dealing With Industrial Revolution 4.0 In BBTKLP Surabaya - Wanda Gema Prasadio Akbar Hidayat (Journal of Social Science and Business Studies, 2023)
This study aims to knowing and analyze the community satisfaction index for public services; and proposed priority improvements to public services as an effort to increase public satisfaction in the face of the Industrial Revolution 4.0 at ths Center for Environmental Health and Disease Control Engineering Surabaya. Samples in this study were taken as many as 90 samples, namely 90 people (community) users of public services at the Center for Environmental Health and Disease Control Engineering Surabaya. This type of research is qualitative research with data analysis methods using descriptive analysis. The conclusions of this study are: (1) the value of the Community Satisfaction Index for public services of 3,211 with an Community Satisfaction Index conversion value of 80.275% this means that the assessment of the performance of public servants is included in both categories; (2) the quality of public services is not appropriate or unsatisfaction to the community, shown from the level of conformity, where the average of each variable or element in public service is still below the level of conformity (<100%); and (3) based on Importance Performance Analysis (IPA), proposed priority improvements to public services a, namely improvements to the simplicity of service mechanisms, clarity in the flow of procedures, the level of conformity of procedures adopted by established procedures, the level of employee ability, the level of speed of service complaints, the level of speed in resolving complaints, and the functioning of the electronic / online service system. Keywords: Public Services, Community Satisfaction Index, Importance Performance Analysis (IPA)